Determination of thermal expansion coefficient for thermoelectric CaMnO3 with a shadow method - C Boonsri; P Limsuwan; P Buranasiri (My University, 2020)
We have measured thermal expansion coefficient of a bulk CaMnO 3 thermoelectric module with a cylindrical shape, using a shadow method.The CaMnO 3 module has been heated from the room temperature up to 773 K.At each temperature, the shadow image has been recorded by a CMOS camera and reconstructed with a HoloViewer program in MATLAB.Then the diameters of the module have been obtained at different temperatures in the region 300-773 K. Finally, we have determined the linear thermal expansion and the thermal expansion coefficient for CaMnO 3 .Our results demonstrate that the expansion coefficient for the bulk CaMnO 3 thermoelectric module depends linearly on the temperature in the region under study.
Keywords: Advanced Thermoelectric Materials and Devices